Research and practice of AI-based teacher-student service platform: a case study of Nanjing Audit University - WU Xin; WANG Weiye (Tongxin xuebao)
Take Nanjing Audit University as an example to investigate the application of an AI-based service platform in enhancing the efficiency and quality of university service platforms and improving the satisfaction of teachers and students. The research aims to address issues such as inefficiency and inaccurate responses in existing service channels. The platform was divided into three layers, data collection, data processing, and user interaction. Based on the RAG framework, search and generation modules were constructed, and multiple entry points were established on the basis of a local knowledge base to provide real-time online services around the clock. The results indicate that the platform significantly improves the satisfaction of teachers and students, effectively resolves service challenges, and promotes teacher-student interaction.